Relationship between prognostic nutritional index and asthma: a cross-sectional analysis - Jiang, Zhimeng; Zhu, Xingyu; Jiang, Huixin; Zhao, Donglin; Tian, Jianwei (Frontiers in Nutrition, 2025)
Background and objectiveAsthma is a chronic disease characterized by inflammation of the airways. The association between nutritional status, inflammation, and asthma has been well-documented, yet the relationship between the Prognostic Nutritional Index (PNI) and asthma remains unclear. This is a study to see whether there is a relationship between PNI and asthma prevalence.MethodsThe present study employed data from the National Health and Nutrition Examination Survey (NHANES) between 2017 and 2020, including a total of 7,869 adult participants were included in the analysis. Participants were categorized into four quartiles based on PNI levels. A multivariable regression model was employed for the purpose of evaluating the correlation between PNI and asthma. In order to ascertain the stability of the association across different populations, subgroup analyses were performed.ResultsHigher PNI levels were significantly associated with lower asthma prevalence. In the complete adjusted model, each additional unit of PNI was associated with a 3% reduction in the prevalence of asthma [0.97 (0.95, 0.99)]. Trend analysis indicated a significant negative correlation between PNI and asthma (p for trend = 0.0041). Subgroup analyses showed a consistent negative association across different populations.ConclusionThe findings of our study indicated that lower PNI values were linked to an elevated odds prevalence of asthma. Early nutritional intervention and inflammation management in high-risk populations with low PNI may reduce the incidence and severity of asthma. Future prospective studies are needed to confirm this relationship.